Innovation and Quality of Business Scale Based on Blue Economy in the Coastal Area of Bilato, Indonesia - Alamsyah Muhammad Fuad; Subhan Andi; Jafar Muhammad Iqbal; Arifuddin; Fikri Muhammad Ali (ECONOMICS)
This study thoroughly examines and analyzes the potential of small and medium-sized enterprises (SMEs) involved in Nike fish (Ikan Nike) in the Bilato coastal area of Indonesia. Several aspects are used as indicators to assess the extent of this potential, including innovation, scale quality, and the application of the blue economy concept. The methodology employed is qualitative, also known as interpretative research, naturalistic research, or phenomenological research. The results of this study indicate a significant and positive improvement among the SMEs involved in Nike fish, particularly in terms of innovation, which encompasses product innovation, sales media innovation, and environmental innovation. Additionally, there has been notable development in scale quality, as evidenced by increases in income, sales, and business profits. Furthermore, the SMEs participating in the Nike fish group consistently implement the blue economy concept as a means of ensuring sustainability and balance in preserving the environment in the Bilato coastal area. This approach not only enhances economic value but also contributes to social and ecological benefits.